'It Takes Me Half a Bottle of Whisky to Get through One of Your Assignments': Exploring One Teacher Educator's Personal Experiences of Dyslexia. (13th January 2015) - Glazzard, Jonathan; Dale, Kirsty
Abstract : This article uses a life history approach to explore personal experiences of dyslexia of one higher‐education lecturer and its impact on her professional identity. The informant is currently employed as a lecturer of initial teacher training in a UK university. She worked as a primary school teacher for over a decade prior to embarking on an academic career in teacher education. The informant draws on her own experiences as a pupil, teacher and lecturer, and additionally, she presents accounts of student teachers with dyslexia drawn from her current professional context. Although the data are not generalizable, the account nevertheless illustrates the positive impact of the social model of disability for the informant and her students who had been identified as dyslexic during their initial training as teachers. Additionally, the account also illustrates the ways in which teachers' personal experiences of dyslexia can shape professional identities in very positive ways. Implications for both teacher training and pedagogic approaches in schools to support learners with dyslexia are drawn out of the narrative. Copyright © 2015 John Wiley & Sons, Ltd.